Intake valve flow optimization for single cylinder four stroke petrol engine - Azah Fadhilah, Ramly (2008)
Optimizing airflow performance during intake valve process is the main purpose for this project. Research had using two previous works as guidance and starting point to setting and achieving targeted limit of optimized airflow, 0.0201075 m³/s. modifications on inlet valve, inlet port of intake system had been done, and original cylinder head Ex5 geometry had been used before turning into 3D modeling as to achieve objective. Analysis was done in CFD simulation and experimental using SuperFlowbench machine. This analysis also reported differentiation that occurs during both analyses around 0.045 % in average where experimental result cannot achieve targeted limit due to some realistic condition. Fabrication of intake valve and intake port also were made to do analysis on experimental based on the modify design. This being done after simulation analysis, modeling design was using to be fabricated and analyze the model on flow bench machine to verify simulating result. This analysis could be used to increase efficiency of volumetric flow rate and maximizing usage of air fuel in combustion process, which reduce emission to environment. Even though air flow have been optimized on its intake valve and port, but still intake system could be improve by considering other parts of Ex5 engine such as intake manifold.